Investment, autonomous demand and long run capacity utilization: An empirical test for the Euro Area - Ettore Gallo (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
In recent years, the role attached to the autonomous components of aggregate demand has attracted rising attention, as testified by the development of the Sraffian Supermulti plier model (SSM) and the attempts to include autonomous demand in the Neo-Kaleckian model. This paper reviews and empirically tests the validity and the policy conclusions of the two models in the Euro Area. First, we theoretically assess whether the SSM may con stitute a complex variant of the Neo-Kaleckian model. In this sense, it is shown that results compatible with the SSM can be obtained by implementing a set of mechanisms in a modified Neo-Kaleckian model, leading to the convergence towards a desired rate of utilization. Furthermore, the chief diffierence between the models is recognized to be the role attached to the rate of capacity utilization in the long run. Second, the paper empirically tests the main implications of the models in the Euro Area, based on Eurostat data. In particular, the discussion outlines the short and long-run relation between autonomous demand and output, by testing both the cointegration and the direction of causality between the two with a VECM model. Moreover, the role accounted by both theories to the actual rate of capacity utilization and its discrepancies from the normal rate is empirically assessed, through a time-series estimation of the Sraffian and Neo-Kaleckian investment functions. While confirming the theoretical relation between autonomous demand and output in the long run, the results show that the dynamics of the rate of capacity utilization still plays a key role in the short-run adjustment mechanism - despite its stationary behaviour in the long term. Therefore, admitting that Keynesian results may hold even after the traverse, our work suggests to be Kaleckian in the short run and Sraffian in the long run.
Keywords: B51; E11; E12; O41; O47; O52; 330; distribution; effective demand; Eurozone; growth; Neo-Kaleckian; Sraffian; Supermultiplier